Where is the Lesion? Glomus Tumours of the Hand - Chris Yuk Kwan Tang; Timothy Tipoe; Boris Fung (Archives of Plastic Surgery, 2013)
Glomus tumours are vascular hamartomas that are commonly found in the hand, particularly the subungual region. They appear as solitary or multiple tumours, and often present as a bluish discoloration of the nail plate. Different diagnostic tests are outlined, as well as imaging studies such as magnetic resonance imaging and ultrasound. Misdiagnosis and delayed diagnosis of these tumours are common, while a familial tendency is a potential risk factor but not yet proven. Complete surgical excision often results in complete symptomatic relief, while recurrences are largely due to incomplete excision or the growth of a new glomus tumour. This article aims to review the key aspects of glomus tumours and provide a diagnostic algorithm so that the lesion can be recognized and treated earlier.